Understanding the experiences of patients with cancers in hospitals during COVID‐19 pandemic in China: A qualitative research study. Issue 1 (26th September 2021) - Chen, Xing; Deng, Wenyu; Zhou, Wenjuan; Liu, Ying; Chen, Jinfeng; Gao, Yuan; Xiao, Kuirong; Man, Lin; Qu, Wanting; Zeng, Hongjuan; Ye, Sha
Abstract: Aim: To explore the experiences of patients with cancers in hospitals during the COVID‐19 pandemic. Design: A qualitative research study. Methods: Using a phenomenological approach, we enrolled 22 patients with cancers in the Hunan Cancer Hospital from 20 February 2020 to 10 April 2020. The interviews were conducted face‐to‐face and were analysed by Colaizzi's 7‐step method. This study aligns with the COREQ checklist. Results: The experiences of patients with cancers in hospitals during the COVID‐19 pandemic can be categorized into four major themes: (1) emotional changes; (2) delays in visiting hospital; (3) barriers to accessing medical care services, and (4) inconvenience related to logistics services.